Bridging Global Frameworks and Local Challenges : The UN’s Role in Implementing the Sustainable Development Goals in Iraq - Ali, Lima Omed; Kočí, Kateřina; Přikryl, Pavel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines how a global agenda, the Sustainable Development Goals (SDGs), traverses a fragile, post-conflict setting through a case study of Iraq from 2015 to 2024. Drawing on localization theory as the primary analytical lens, I regard the SDGs as international norms that domestic actors must interpret, adapt, and institutionalize rather than merely adopt. A qualitative single-case design supported the research, based on a document analysis of Iraqi government strategies and laws, including Vision 2030 and National Development Plans, as well as UN country frameworks and programs, VNRs, and relevant academic reports. The key finding has been a clear pattern: Iraq achieved formal alignment with the SDGs and created new coordination bodies, but implementation remains uneven. The main barriers identified are institutional weakness and fragmented responsibilities, stalled decentralization, frictions between the center and the periphery, a rentier economy with limited diversification, and inadequate data and monitoring. In a brief, the UN’s contribution is most effective when support is tightly tailored to Iraq’s political economy and followed through with day-to-day coordination. Otherwise, delivery stalls due to either bureaucratic hurdles or low domestic ownership. The thesis concludes that progress depends on clarification of mandates and accountability across national and sub-national institutions and their UN counterparts, shielding follow-up from political turnover, piloting of reforms in more stable provinces (e.g., KRG) before scaling, more profound decentralization for provinces to plan, execute, and monitor, paired with diversification and human-capital investments in the manner through which SDG implementation could function in reality.
Vedoucí práce: Kateřina Kočí
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses